2021
DOI: 10.1080/19490976.2021.1966262
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of the gut microbiome in allogeneic hematopoietic stem cell transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is used for the treatment of hematologic cancers and disorders. However, graft-versus-host disease (GVHD) in which the donor immune cells attack the genetically-disparate recipient is a significant cause of morbidity. Acute GVHD is an inflammatory condition and the gastrointestinal system is a major organ affected but is also tied to beneficial graft-versus-tumor (GVT) effects. There is increasing interest on the role of the microbiome on immune fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…The microbiome mainly dictates the amplitude of the inflammatory response and its outputs [14]. Intensive chemotherapy [37][38][39] and HCT [40,41] in general, are associated with oral and gut microbial dysbiosis (lower microbial diversity and outgrowth of opportunistic pathogens). Microbial dysbiosis is considered to play a role in severe (post-transplant) complications such as bloodstream infections or bacteremia [37,42] and pulmonary infections [43], graftversus-host disease [44,45], perturbed immune reconstitution [46], even relapse (higher abundance of mostly Eubacterium limosum) [47] and non-relapse mortality [40].…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…The microbiome mainly dictates the amplitude of the inflammatory response and its outputs [14]. Intensive chemotherapy [37][38][39] and HCT [40,41] in general, are associated with oral and gut microbial dysbiosis (lower microbial diversity and outgrowth of opportunistic pathogens). Microbial dysbiosis is considered to play a role in severe (post-transplant) complications such as bloodstream infections or bacteremia [37,42] and pulmonary infections [43], graftversus-host disease [44,45], perturbed immune reconstitution [46], even relapse (higher abundance of mostly Eubacterium limosum) [47] and non-relapse mortality [40].…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…Fluoroquinolone prophylaxis has been associated with decreased rates of infection in patients with neutropenia, though most studies do not show an overall survival benefit [2]. However, fluoroquinolone prophylaxis has been associated with the development of drug resistant infections, drug toxicities, adverse changes in the gut microbiome and increased Clostridioides difficile colitis rates, and adverse impacts on graft-versus-host disease (GVHD) and transplant outcomes [3–5]. Balancing infection prevention strategies with benefits and risks of antimicrobial prophylaxis is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) remains a curative strategy for a variety of hematologic diseases. During the process, recipients are usually exposed to chemotherapy, broad‐spectrum antibiotics, and immunosuppressive agents, which are all known to affect the dynamic changes in the gut microbiota 1–3 . There is growing evidence that the gut microbiota is linked to the prognosis of patients undergoing allo‐HSCT 4 .…”
Section: Introductionmentioning
confidence: 99%
“…During the process, recipients are usually exposed to chemotherapy, broad‐spectrum antibiotics, and immunosuppressive agents, which are all known to affect the dynamic changes in the gut microbiota. 1 , 2 , 3 There is growing evidence that the gut microbiota is linked to the prognosis of patients undergoing allo‐HSCT. 4 Published studies on the gut microbiota in allo‐HSCT have indicated that the diversity of the gut microbiota is associated with the incidences of mortality and complications as well as the speed of immune reconstitution.…”
Section: Introductionmentioning
confidence: 99%